Implementasi Metode Iqra’ Dalam Meningkatkan Pengenalan Huruf Hijaiyyah Pada Anak Usia Dini Di TK Az-Zahra Mondang - Nur Baiti; Mira Yanti Lubis; Silfa Hafizah Pulungan (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Based on the results of research carried out by the author, it can be concluded that (1) The ability to recognize hijaiyyah letters in early childhood at the Az-Zahra Mondang Kindergarten has not yet developed (BB) as much as 1 child or 4.17%, the ability to recognize hijaiyyah letters in early childhood begins Developing (MB) 11 children or 45.83%, the ability to recognize hijaiyyah letters in early childhood Develops According to Expectations (BSH) 10 children or 41.67%, while the ability to recognize hijaiyyah letters in early childhood Develops Very Well (BSB) 2 children or 8.33%. (2) The ability to recognize hijaiyyah letters in early childhood using the iqra' method at Az-Zahra Mondang Kindergarten in cycle I classically, namely Not Yet Developed (BB) there are no children, the ability to recognize hijaiyyah letters in early childhood Begins to Develop (MB) 7 children or 29.17%, the ability to recognize hijaiyyah letters in early childhood is developing according to expectations (BSH) 12 children or 50.00%, while the ability to recognize hijaiyyah letters in early childhood is developing very well (BSB) 5 children or 20.83%. In cycle II, classically, namely Not Yet Developed (BB) there were no children, the ability to recognize hijaiyyah letters in early childhood began to develop (MB) 1 child or 4.17%, the ability to recognize hijaiyyah letters in early childhood Developed According to Expectations (BSH) 10 children or 41.67%, while the ability to recognize hijaiyyah letters in early childhood is developing very well (BSB) for 13 children or 54.17%. So it can be concluded that implementing the iqra' method can increase the recognition of hijaiyyah letters in early childhood at Az-Zahra Mondang Kindergarten.